PAA Modified Upconversion Nanoparticles for Highly Selective and Sensitive Detection of Cu2+ Ions - Su, Shaoshan; Mo, Zhurong; Tan, Guizhen; Wen, Hongli; Chen, Xiang; Hakeem, Deshmukh A. (Frontiers in Chemistry, 2021)
Detection of the Cu2+ ions is crucial because of its environmental and biological implications. The fluorescent-based organic sensors are not suitable for Cu2+ detection due to their short penetration depth caused by the UV/visible excitation source. Therefore, we have demonstrated a highly sensitive and selective near-infrared (NIR) excitable poly(acrylic acid) (PAA) coated upconversion nanoparticles (UCNPs) based sensor for Cu2+ detection. We construct the PAA modified Na(Yb, Nd)F4@Na(Yb, Gd)F4:Tm@NaGdF4 core-shell-shell structured UCNPs based sensor via a co-precipitation route. The upconversion emission intensity of the PAA-UCNPs decreases linearly with the increase in the Cu2+ concentration from 0.125 to 3.125 μM due to the copper carboxylate complex formation between Cu2+ and PAA-UCNPs. The calculated detection limit of the PAA-UCNPs based sensor is 0.1 μM. The PAA-UCNPs based sensor is very sensitive and selective toward detecting the Cu2+ ions, even when the Cu2+ co-exist with other metal ions. The EDTA addition has significantly reversed the upconversion emission quenching by forming the EDTA-Cu2+ complex based on their greater affinity toward the Cu2+. Therefore, the PAA-UCNPs based sensor can be a promising candidate for Cu2+ detection because of their higher sensitivity and selectivity under 980 nm NIR excitation.